Implications of Internal Factors and Employee Intrinsic Motivation on Employee Performance - Nurlina Nurlina (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2021)
Leadership and work environment has a large part in motivating each member organization toward the company's goals. A leader should implement a leadership style to manage his subordinates because a leader will significantly affect the Organization's success in achieving its goals. No less important will be this is the role of the work environment itself which woke up, the work environment is one of the essential components within the employees finish his work. Here is the working environment: the immediate vicinity of the workers that can affect him in the exercise of duties charged. This research was conducted at PT. Pegadaian Regional VI of Makassar city with 30 research sample of respondents are the employees of PT. Pegadaian Regional VI. This Research is variable work environments (X1.1), the leadership style (X1.2), intrinsic motivation (X ), and the performance of the employees (Y). research using the method of multiple linear regression analysis with data collection using questioners. This research shows that the work environment does not affect employees' performance, leadership style, and intrinsic motivation the employee's account. Leadership styles and the variable is the variable that the dominant influence on the dependent variable.